SISTEM PENGELOLAAN SEBARAN DATA PRODUK DAN KLIEN DENGAN IMPLEMENTASI PETA ONLINE - Nur Alamsyah (NUANSA INFORMATIKA, 2019)
The research design of software aims to help managing data products and data clients in PT .Ussi Bandung - West Java. This research is the impact of the advance of technology resulting in some works to handle or it is assisted by the technology. Moreover by the computer, it improves efficiency and quality in work. By the use of computer, people will be easy in finishing the job in various fields for example the management of product data and client that use web based application recording product and client. In practice, computer technology could save the data quickly and correctly and also it displays the data in detail and more informative.  As a result, all information clients will be recorded optimally and more informative. This research is also expected to provide information about all matters relating to clients products or starting development products, the implementation of products , launching products , etc. Keywords : A computer system , products clients , recording the data